Non-destructive testing of meat using interdigital and meander type sensors - Syed Abdullah, Sharifah Sakeenah; Mohammed Osman Salleh, Sara; Sidek, Khairul Azami (Universiti Teknikal Malaysia Melaka, 2016)
Adulterations in labeling of meats, especially for halal product consumers can be considered as a major problem. This study is designed to qualitatively differentiate between beef and pork meats using a non-destructive method. A total of 250 grams of raw beef and pork meat samples have been collected from different parts of the meats. Unique characteristics such as resonance frequency, S-parameter and impedance of the meats were detected and classified by two types of sensors. The sensors which are planar interdigital and planar meander sensors have been fabricated using IPC and FR4 substrate respectively. Testing of the beef and pork meat was done separately. The performance of the system was reliant on the accuracy obtained from the sensors based on the mentioned characteristics. When using the interdigital sensor, it has been found that the average impedance of the pork meat parts is always higher than the average impedance of the beef meat parts of 2.71MΩ as compared to 1.68MΩ. This can be due to the fact that the beef meat contains more density of muscles compared with the pork meat. Meanwhile, when using the grounded meander sensor, the average S21 (dB) was up to -16.177dB for pork meat and -19.515dB for beef meat. The results have shown that the interdigital and meander sensors can be used to differentiate between beef and pork meat. In the future, these sensors may be developed into a portable device known as a non-destructive test to distinguish beef from pork meat.